Differentiation between the like and unlike isomers of dimethyl 3,4-di(p-anisyl)adipate using 1H NMR spectroscopy - Campos Ivan P. de A.; Sakata Solange K.; Viertler Hans; Pardini Vera L. (Journal of the Brazilian Chemical Society, 2000)
The differentiation between the like and unlike isomers of the title compound, achieved by combined use of ¹H NMR spectroscopy, spectral simulation and Molecular Mechanics, correlated by means of the Altona Equation (a generalized version of the Karplus Equation), is reported herein.